2022
DOI: 10.1021/acs.jafc.2c06200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Metabolomic Analysis of Soybean Nodule Number Improvements with the Use of Water-Soluble Humic Materials

Abstract: Water-soluble humic materials (WSHMs) can enhance the nodule numbers of soybean plants. In this study, targeted metabolomics and transcriptomics were used to understand this mechanism. Results showed that 500 mg/L WSHM increased the adsorption and colonization of rhizobia in soybean roots. High-performance liquid chromatography and targeted metabolomics showed that WSHMs could regulate the content and distribution of endogenous hormones of soybean plants at the initial stage of soybean nodulation. Transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that HA promotes plant growth by increasing the concentration of IAA in plants, 21,47 and WSHM did enhance soybean nodulation by regulating the plant hormones, including IAA, gibberellin acid, abscisic acid, jasmonic acid, and salicylic acid. 21 In this study, RT-qPCR was performed for the key genes in the isoflavonoid synthesis pathway (Figure 5). The significantly up-regulated expression of all of the examined genes at the sixth hour in WSHM treatment was consistent with the enhanced flavonoid synthesis observed in the analysis of root exudates.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have shown that HA promotes plant growth by increasing the concentration of IAA in plants, 21,47 and WSHM did enhance soybean nodulation by regulating the plant hormones, including IAA, gibberellin acid, abscisic acid, jasmonic acid, and salicylic acid. 21 In this study, RT-qPCR was performed for the key genes in the isoflavonoid synthesis pathway (Figure 5). The significantly up-regulated expression of all of the examined genes at the sixth hour in WSHM treatment was consistent with the enhanced flavonoid synthesis observed in the analysis of root exudates.…”
Section: Discussionmentioning
confidence: 86%
“…18,19 Based upon the previous studies, the activity of HS as biostimulants has been explained by (1) inducing changes in root morphology and modulate plant nutrient acquisition, 20 (2) regulating the synthesis of hormones in plants, 21 (3) improving growth and survive of rhizobia by regulating protein synthesis and quorum sensing, 21−25 and (5) inducing the expression of nodulation genes by the isoflavonoid-like molecules in HS. 22,25 Except the effects on plants and rhizobia mentioned above, WSHM or FA treatment also significantly reshaped the transcript profiles of plants, 21,25 inevitably influencing plant metabolism and the composition of root exudates, which are the primary regulators of plant−rhizosphere dialogue, mediating the exchange of substances and information between plants and rhizosphere microorganisms. 26 Previous studies have evidenced that soybean root exudates changed the expression of genes relating to two-component system, chemotaxis, and metabolic adaptation processes of Bradyrhizobium diazoef f iciens.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the data obtained in the present study suggest that, instead of ACC, WSHM directly regulates ethylene to promote soybean nodulation. In addition, recent studies have shown that decreasing ethylene content in nodules is also critical for the development of bacteroid and for their ability to fix nitrogen (Cao et al, 2022; Zhang et al, 2023). Therefore, WSHM might enhance the nitrogenase activity of nodules via the inhibition of ethylene.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that WSHM compensates for BR‐induced nodulation suppression by inhibiting ethylene synthesis as revealed in the present study. Although WSHM could increase the ethylene precursor ACC content in soybean roots (Zhang et al, 2023), it did not represent an increase in ethylene content, as ACC needs to be converted to ethylene under the action of ACC oxidase, and then regulates nodulation in legumes by ethylene signalling (Guinel, 2015). Although it has been found that ACC can act independently of ethylene signalling and may serve as a new hormone molecule (Mou et al, 2020), there is no report on ACC directly regulating nodulation in legumes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation